KEWENANGAN BUPATI TERHADAP PEMBINAAN DAN PENGEMBANGAN BADAN USAHA MILIK DESA / BADAN USAHA MILIK DESA BERSAMA DI KABUPATEN MADIUN (PENDEKATAN FILOSOFIS, SOSIOLOGIS DAN YURIDIS) - Mahmud Rifa'i (Birokrasi Pancasila: Jurnal Pemerintahan, Pembangunan dan Inovasi Daerah, 2022)
Madiun Regency has many villages with BUM Desa/BUM Desa Bersama, and some are encouraged and independently develop the economic potential of existing villages. Most of the BUM Desa/BUM Desa Bersama is given initial capital stimulants from the Village Fund and the Village Fund Budget with the status of the funds belonging to the village community and becoming shares in the BUM Desa/BUM Desa Bersama. However, many BUM Desa/Bum Desa Bersama is not developing well. Therefore, local governments must carry out guidance and development with an appropriate legal basis, both philosophical, sociological, and juridical. The aim of the research is to the importance of the Madiun regent's regulation regarding the guidance and development of village-owned enterprises/co-village-owned enterprises (with a philosophical, sociological, and juridical approach). The research used the juridical-normative method, Focus Group Discussion (FGD), and public hearing. The results of theoretical studies and philosophical, sociological, and juridical foundations The Madiun Regency Government is authorized to regulate the Guidance and Development of BUM Desa/BUM Desa Bersama in Madiun Regency through a Regent Regulation covering the regulation of community rights, obligations, and responsibilities towards the Guidance and Development of BUM Desa/BUM Desa Bersama can bind all Village Heads, Village Apparatus and Village BUM Organizations/BUM Desa Bersama and communities in Madiun Regency.